Free and Immobilised β-Glucosidases in Oenology: Biotechnological Characterisation and Its Effect on Enhancement of Wine Aroma - Fernández-Pacheco, Pilar; García-Béjar, Beatriz; Briones Pérez, Ana; Arévalo-Villena, María (Frontiers in Microbiology, 2021)
In grapes, monoterpenes and norisoprenoids are in the form of nonvolatile compounds, flavourless glycosides which could enhance the aroma of wines after its hydrolysis using β- glucosidad enzymes. It is known that the use of immobilised enzymes offers advantages such as reusability and easy recuperation. In this study, a commercial β-glucosidase was immobilised by absorption in sodium alginate. Biotechnological characteristics and terpen hydrolysis (hydrolysis aroma precursors) in muscat wines were studied after treatment with both free and immobilised commercial β- glucosidase with two different concentrations. It was revealed that both forms shared an optimal pH (4.5) and a maximum temperature (64ºC), even an increment on the activity between 40ºC–60ºC. A similar Km value has been determined while Vmax from the immobilised enzyme was higher than the free (3.35 and 2.52 μmol min-1 mg-1, respectively). Additionally, the immobilised enzyme showed a better hydrolytic activity during 24h, and its reusability has been proven. Regarding enzymatic hydrolysis in grape must, the best results were observed for the highest concentration of free β-glucosidase although glucose release was also determined for the immobilised enzyme along the days. In contrast, maximum activity was reached by the immobilised β-glucosidase in less time but in no case equalled the free ones. Finally, volatile compound liberation in wines treated with free or immobilised enzymes was analysed using HRGC-MS. Liberation for both enzymes and the greatest concentrations of some volatiles were detected when a double dose of the free β-glucosidase was used. Nevertheless, the wines treated with the immobilised β-glucosidase showed a high concentration of some volatile compounds such as nerol or geraniol.